Analisis Keterampilan Berpikir Kritis Siswa di Sekolah Menengah Kejuruan (SMK) Menggunakan Metode Ekspositori dalam mata Pelajaran Sanitasi, Hygiene, dan Keselamatan Kerja (SHKK) - Sukriyadi, Sukriyadi; Burhanuddin, Burhanuddin; Mustofa, Hisbulloh Als; Bilad, Muhammad Roil (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the critical thinking skills of vocational high school (SMK) students and to identify the factors influencing their development within the context of expository teaching in the subject of Sanitation, Hygiene, and Work Safety (SHWS). The research employed a one-shot case study design using both quantitative and qualitative approaches. A total of 20 tenth-grade students from a public vocational high school in Central Lombok were selected as research participants. Quantitative data were collected through open-ended tests designed to measure critical thinking skills across five key indicators, while qualitative data were obtained from open-ended interviews with subject teachers. The results showed that students' critical thinking skills fell into the